Debunking the myth of the teacher performance plateau. (April 2019) - Goodwin, Bryan; Slotnik, William J.
There is a long-held but inaccurate belief that new teachers' expertise and talent is mostly innate and that it peaks and plateaus within their first few years of teaching. William Slotnik and Bryan Goodwin explain that school systems need to abandon this conventional wisdom and instead build true talent development systems that support the careerlong development of teachers' professional practices. The path forward requires school districts to understand how people develop expertise and create ways for teachers to develop their talent at all stages in the process .